Dietary polyphenols turn fat "brown": A narrative review of the possible mechanisms. (March 2020) - Hu, Jiamiao; Wang, Zhenyu; Tan, Bee K.; Christian, Mark
Abstract: Background: Inducible brown adipocytes called beige adipocytes are found in white adipose tissue (WAT) depots. They express functional UCP1 and have thermogenic fat-burning capacities as also found in classical brown adipocytes in response to various stimuli. Beige adipocytes may also secrete certain factors that affect WAT function and systemic metabolism. Therefore, a white-to-brown fat conversion could be a novel therapeutic avenue for tackling obesity and metabolic disorders. Scope and approach: In this review, we examine the evidence supporting the concept that the anti-obesity action attributed to polyphenols might be contributed by their stimulation of WAT browning, and discuss the possible underlying mechanisms involved in this action. Key findings and conclusions: Current evidence, mostly derived from animal models, strongly supports that dietary polyphenols may play roles in the browning of WAT. Studies also show multiple signaling pathways, receptors, and transcription factors have been associated with the browning effects of dietary polyphenols. In conclusion, polyphenol compounds and their principal metabolites may contribute to counteracting human obesity via promoting WAT browning. Highlights: Dietary phenolics promote white-to-brown fat conversion. Multiple signaling pathways, receptors, and transcription factors are involved. Polyphenol-induced browning of WAT may also occur in humans.